UN CRITERIO PARA IDENTIFICAR DATOS ATÍPICOS - Jiménez Moscoso, José Alfredo (Revista Colombiana de Estadística, 2004)
This paper present a method to determine the observations that are outliers in a model of multiple linear regression; these data will be established according to the change that is presented on the sum of the squares of residual of the model.